ANALISA TINGKAT PREVALENSI DAN DERAJAT INFEKSI PARASIT PADA IKAN KERAPU MACAN (Ephinephilus fuscoguttatus) DI LOKASI BUDIDAYA BERBEDA - Marzuki Musyaffak; Indah Wahyuni Abida; Firman Farid Muhsoni (Jurnal Kelautan, 2010)
Fish is the potential protein source for human. People consumption of fish requires attention related to whether the fish is safe to consume. This research is aimed at finding kind of parasite attack Groupers (E. fuscoguttatus) and the prevalence and the infection level in the different farming location. The research method used that is by taking Groupers size between 10 cm - 35 cm as many  fish from all population in each location with the assumption of percentage the prevalence used was 10%. Sample then analyzed for amount and type of parasite attacked and determined level of prevalence and degree of parasite infection. Result showed the type of parasite attack Groupers are Anasakis sp., Diphyllobothrium sp., Caligus sp., Diplectanum sp., Ergasillus sp., and Argulus sp. The different location of farming didn’t influence the parasite prevalence degree in Groupers. It is known that in location 1 in Lamongan, the prevalence level is 60% and the amount of fish attacked is 12, while in location 2 which is in Situbondo regency the prevalence degree is 50% with 10 fish attacked. t-test result showed that the level of infection degree did not differ perhaps because of the water condition quality between two location was relatively similar and still in the normal category, and also farmers have known the farming techniques well. Key Words : Prevalence, Degree of parasite infection, Groupers